Study of the different types of images on the short poems - hamid Jafari GhariyehAli; مهسا کشاورز (مطالعات زبانی و بلاغی)
Since a long time ago up to now  there has been a short form of poem. This form which has changed to one of the species of Persian poem in present time, has been regarded more in recent years and is being independent. Disregarding names called for this form of poem before contemporary period, in present time, from Nima up to now some items such as design, ultra-modern, massage poem and… are allocated to its special one. Sometimes these special meanings integrate with general meaning of short poem and lead to some ambiguities to differentiate them. Therefore, this research studies different images from function, structure and thought level's point of view in several forms of short poem by introducing style characteristics of short poem in contemporary period while relies on two clear characteristics such as laconism and imagination and then analysis and description are used. This research aims to recognize auesthetic characteristics especially imagination in contemporary literal flows and then short form of every flow in its pioneer poem. Author finally concludes that composing short poem purposefully and especially is much different from random short poem and this difference is effective on choosing poem images.